GENDER BIAS IN CHOOSING STEM STUDIES : Received: 26th August 2021; Revised: 09th December 2021, 09th March 2022; Accepted: 10th March 2022 - Monsalve, Laura Lorente; Conde, Laura Gonzalvo (PUPIL: International Journal of Teaching, Education and Learning, 2022)
The gender bias in STEM exists, and this work intends to make this reality visible. The principal objectives of the study are to reduce the gender gap in STEM studies and learn about experiences lived around the STEM field reported by women. For this, a qualitative research method has been created in the form of an interview, which helps us answer the questions raised from the life stories told by the fourteen girls and women interviewed, all of them belonging to different age ranges, to be able to observe and analyze gender bias when choosing STEM studies. The data resulting from the research are the least bleak in the framework of the development of gender equality. A minimum change could be expected. However, the changes we observe are specific. We must remember that most of the participants have alluded to society and culture to explain the bias. The generational shift that is observed through the interviews is minimal. Although the educational administrations seek absolute equality and promotion of research and development of ICT among girls and adolescents, we must make visible that these actions need a more significant effort to be part of the educational community.